Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1117/1.jbo.19.1.011009
|View full text |Cite
|
Sign up to set email alerts
|

Using optical profilometry to characterize cell membrane roughness influenced by amyloid-beta 42 aggregates and electric fields

Abstract: Abstract. The membrane roughness of Neuro-2a neroblastoma cells is measured by using noninterferometric widefield optical profilometry. The cells are treated with the fibril and oligomer conformers of amyloid-beta (Aβ) 42, which is a peptide of 42 amino acids related to the development of Alzheimer's disease. We find that both the Aβ42 fibrils and Aβ42 oligomers reduced the cell membrane roughness, but the effect of Aβ42 oligomers was faster and stronger than that of the fibrils. We also apply direct-current e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…In our previous works 3 , 12 , we demonstrated that the membrane roughness of neuroblastoma cells is sensitive to various external stimulations, including amyloid peptides of different conformations, electric fields, an anti-cancer drug Taxol, gold nanoparticles, and a hypertonic solution. Nonetheless, the treatments used in those previous works were all solution-based.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…In our previous works 3 , 12 , we demonstrated that the membrane roughness of neuroblastoma cells is sensitive to various external stimulations, including amyloid peptides of different conformations, electric fields, an anti-cancer drug Taxol, gold nanoparticles, and a hypertonic solution. Nonetheless, the treatments used in those previous works were all solution-based.…”
Section: Discussionmentioning
confidence: 97%
“…The whole NIWOP system was placed in a temperature-controlled microscope cage that provided a constant-temperature environment (37 ± 0.5 °C) for the live-cell experiments. More details about the operation of the NIWOP system can be found in our previous publications 3 , 9 12 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Lulevich et al revealed that amyloid-β (Aβ), the key pathogenic protein of Alzheimer’s disease, increases the stiffness of mouse neuroblastoma cell N2a by using atomic force microscopy [ 2 ]. Pan et al found that Aβ could reduce the membrane roughness of neuroblastoma, and electrical stimulations reversed this effect [ 3 ]. But the detailed mechanisms were not clear.…”
Section: Introductionmentioning
confidence: 99%